2011
DOI: 10.1103/physrevb.84.064403
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-crystallographic phase diagram of the superconducting parent compound Fe1+xTe

Abstract: Through neutron diffraction experiments, including spin-polarized measurements, we find a collinear incommensurate spin-density wave with propagation vector k = (0.4481(4) 0 1 2 ) at base temperature in the superconducting parent compound Fe1+xTe. This critical concentration of interstitial iron corresponds to x ≈ 12% and leads crystallographic phase separation at base temperature. The spin-density wave is short-range ordered with a correlation length of 22(3)Å, and as the ordering temperature is approached it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

36
221
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(258 citation statements)
references
References 56 publications
36
221
1
Order By: Relevance
“…11,25,28 For y < y c ≈ 0.1, the structure is monoclinic, with two different Fe-Fe in-plane bond lengths that match up with the alternating antiferromagnetic and ferromagnetic bonds of the collinear magnetic structure. 11,18,41 For y > y c , the structure is orthorhombic, with a single Fe-Fe bond length; the corresponding magnetic structure is found to be helical.…”
Section: A Tuning Of the Magnetic Ordermentioning
confidence: 99%
See 4 more Smart Citations
“…11,25,28 For y < y c ≈ 0.1, the structure is monoclinic, with two different Fe-Fe in-plane bond lengths that match up with the alternating antiferromagnetic and ferromagnetic bonds of the collinear magnetic structure. 11,18,41 For y > y c , the structure is orthorhombic, with a single Fe-Fe bond length; the corresponding magnetic structure is found to be helical.…”
Section: A Tuning Of the Magnetic Ordermentioning
confidence: 99%
“…11,18,41 For y > y c , the structure is orthorhombic, with a single Fe-Fe bond length; the corresponding magnetic structure is found to be helical. 11, 25 Mizuguchi et al 28 have recently demonstrated with high-resolution x-ray diffraction that the boundary between the orthorhombic and monoclinic phases can also be crossed as a function of temperature for y y c . On cooling from the tetragonal phase, it is possible to transform first to the orthorhombic and then to the monoclinic.…”
Section: A Tuning Of the Magnetic Ordermentioning
confidence: 99%
See 3 more Smart Citations